The Effectiveness of Art Therapy in Reducing Depressive Symptoms among Patients with Mood Disorders - Alisha Nur Salsabila (International Journal of Nursing and Midwifery Research, 2025)
Mood disorders are among the leading causes of disability worldwide, with depression as a core symptom that significantly impairs emotional, social, and functional well-being. Although pharmacological treatment is the primary approach, many patients continue to experience persistent depressive symptoms, highlighting the need for complementary non-pharmacological interventions. This study aimed to evaluate the effectiveness of art therapy in reducing depressive symptoms among patients with mood disorders. A quasi-experimental pretest-posttest design was employed involving patients diagnosed with mood disorders who exhibited depressive symptoms. Participants received a structured art therapy intervention conducted in group sessions twice a week over a six-week period. Depressive symptoms were measured before and after the intervention using a standardized depression assessment instrument. Data were analyzed using appropriate inferential statistical tests to compare pre-intervention and post-intervention depression scores. The results indicated a significant reduction in depression scores following the art therapy intervention. Participants showed a shift from higher to lower levels of depression severity after completing the program. Statistical analysis revealed that the difference between pretest and posttest scores was significant (p < 0.05), with a moderate to large effect size, suggesting both statistical and clinical relevance of the intervention. Art therapy was found to be effective in reducing depressive symptoms among patients with mood disorders. These findings support the use of art therapy as a complementary intervention in mental health care settings to enhance emotional expression, self-awareness, and psychological well-being. Integrating art therapy into routine mental health services may contribute to more holistic and patient-centered treatment approaches.